Profit by Fiat - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2012)
If there is no objective value, how can fraud `distort' prices, profit and the normal rate of return?
Keywords: 330; banking; crime; price; profit